The Validity of the SNAP-IV in Children Displaying ADHD Symptoms. (September 2020) - Hall, Charlotte L.; Guo, Boliang; Valentine, Althea Z.; Groom, Madeline J.; Daley, David; Sayal, Kapil; Hollis, Chris
The Swanson, Nolan, and Pelham Rating Scale (SNAP-IV) is a widely used scale that measures the core symptoms of attention deficit hyperactivity disorder (ADHD). However, there are contradictory findings regarding factor structure. Factor structure and measurement equivalence/invariance analysis on parent and teacher SNAP-IV for children referred for an ADHD assessment ( N = 250; 6-17 years), revealed a two-factor structure provided the best fit. SNAP-IV scores were also compared with clinician diagnosis of ADHD and research diagnoses of ADHD and hyperkinetic disorder. Parent ratings of inattention and hyperactivity/impulsivity were good predictors of research but not clinician diagnosis. For teacher ratings, only hyperactivity/impulsivity scores were associated with research and clinician diagnosis. SNAP-IV scores showed high sensitivity but low specificity to clinician diagnosis. The SNAP-IV is a valid outcome measure for use in randomized controlled trials and clinical settings, and is best used as a screening rather than a diagnostic tool for ADHD.